Sex workers and the control of sexually transmitted disease - Day,S; Ward,H (Genitourinary Medicine, 1997)
Objectives: To describe and assess measures to control sexually transmitted diseases (STDs) among sex workers and their partners. Methods: A review of medical, historical and social literature, focusing on selected cases. Results: Measures to control disease in sex workers today are often prompted by concerns about HIV transmission. However, the literature shows that prostitution varies from one place and time to another, together with the risk of sexually transmitted disease. A broad social definition of prostitution rather than a narrow reference to levels of sexual activity is important for effective disease control, as an understanding of the relation between social disadvantage and sexual activity enables the provision of occupational services that sex workers actually want and use. Social prejudice and legal sanctions cause some sex workers and their partners to avoid even the most appropriate and accessible specialist services. Therefore targeted programmes can only complement, and not replace, general measures to control STDs, which are developed for other social groups or the local population as a whole. Conclusions: Sex workers and sex work differ from one place to another and so a single model for STD control is inappropriate. None the less, occupational health risks suggest a general need for specialist services. Where these do not compound the disadvantages that sex workers already suffer, medical services are likely to offer significant benefits in prevention, early diagnosis, and treatment of STDs. As the stigma of prostitution leads many people to remain invisible to services, a general health infrastructure and anti-discriminatory measures will be equally important to effective disease control.